Metode Pengajaran dan Kurikulum Darus Sunnah Sebagai Institusi Hadis Bertaraf Internasional - Usep Dedi Rostandi; Ali Masrur; Rosihon Anwar (AL QUDS : Jurnal Studi Alquran dan Hadis, 2020)
Instructional Methods and Curriculum of Darus Sunnah as an International Hadith InstitutionThis paper delves into "Darus Sunnah as an International Hadith Institution.” This research was conducted to prove that Darus Sunnah is an Islamic boarding schoolexisting at the international level.This research also showed that the educational program of Darus Sunnah used four methods, namely: mudhākarah, halaqah fajriyyah, munazhzhamah, and istijmām.The learning method applied in Darus Sunnah wasstudent-centered, wherein students were required to discuss actively with the mudarris as facilitators. The methods used in this Islamic boarding school dailycomprised: bandongan, sorogan, tahfizh of hadith, tahfizh of Qur’an, and tahfizh of yellow books. The students of Darus Sunnah were also directed to conduct a community service program (PPM) as an ideal of PPM model. This research proved that Darus Sunnah is an international hadith institution. This is proven by the following facts: 1. Darus Sunnah Islamic Boarding School has got a branch in Malaysia since 2012, located in al-Sakinah Eco Resort Kampung Janda Baik, Negeri Pahang, Malaysia. 2. Darus Sunnah Islamic Boarding School has sent dā'i to foreign countries, such as America and Malaysia. 3. The sending of students to Egypt is one proof that Darus Sunnah is an international boarding school. The program to send students to Egypt is in collaboration with the Lido Pesantren 4. Darus Sunnah Islamic boarding school also frequently receives international students especially students who study around Darus Sunnah Islamic boarding school